Transmisi Gelombang pada Pemecah Gelombang Ambang Rendah Ganda - Surendro, Bambang; Yuwono, Nur; Darsono, Suseno (Department of Civil Engineering, Diponegoro University, 2014)
Coastal protection efforts can be done in various ways, among others, by making alow threshold breakwaters (sumerged breakwater). Every building in addition there is certainly no shortage of excess. With several weaknesses breakwater low threshold, then conducted research with the title “Wave Transmission At Low Threshold Dual-breaking waves